Resolving responsibility gaps for lethal autonomous weapon systems - Smith, Patrick Taylor (Frontiers in Big Data, 2022)
This paper offers a novel understanding of collective responsibility for AI outcomes that can help resolve “many hands” and “responsibility gaps” when it comes to AI failure, especially in the context of lethal autonomous weapon systems. The paper achieves this by providing the normative grounds for and a general description of a political conception of responsibility for just war compliance and non-compliance by lethal autonomous weapon systems. Deploying the Unfair Burden Argument, the Agent Constitution Argument, and the Collective Values Argument, the paper shows that we should move away from an interpersonal and ethical understanding of responsibility to a collective and holistic distributive conception of responsibility where we assign various accountability mechanisms and responsibilities to agents in the system on the basis of effectiveness and fairness rather than direct moral responsibility. This new account dissolves the problem of responsibility gaps for lethal autonomous weapon systems and points a way forward towards appropriately and legitimately distributing responsibility through the defense statecraft ecosystem.